1982
DOI: 10.1115/1.3225038
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of Metallic Materials

Abstract: Klesnil and Lucas have been actively involved in research on the basic aspects of fatigue for a score of years and are deservedly well recognized for their many contributions to our knowledge of the topic, particularly in areas of dislocation structures, cyclic stress-strain behavior and crack growth analysis, for example. The present book is organized about these areas of fatigue with which they have dealt and the treatments reflect their perspective. Their views have also been influenced by the works of many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
5

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 0 publications
5
68
0
5
Order By: Relevance
“…Such stress amplitudes represent 79 to 92 % of the fatigue limit for 3 × 10 6 cycles until fatigue fracture. These partial results are in compliance with the measurements of other authors [11,16].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Such stress amplitudes represent 79 to 92 % of the fatigue limit for 3 × 10 6 cycles until fatigue fracture. These partial results are in compliance with the measurements of other authors [11,16].…”
Section: Resultssupporting
confidence: 93%
“…Both identified non-continuities in the cyclic properties of the material are caused by the difference in the mechanism of plastic strain below or above the point of non-continuity. Based on the analysis of deformation processes, it is obvious that the amplitude of plastic strain ε ap consists of the following components [11,17,18]:…”
Section: Problem Analysismentioning
confidence: 99%
“…40,41 However, the Cv of fatigue life data under 95%-75% UTS is 0.6, 0.6, 0.72, 0.74, and 0.54. Thus, there is no clear trend in scatter of fatigue life data for T800/ MTM46 composite laminates, which is far different from the fatigue life data of traditional metallic materials.…”
Section: Tension-tension Fatigue Experimentsmentioning
confidence: 99%
“…Through setting y = lgðSÞ; x = lgN p;g , Q = lgðC p;g Þ=m p;g , and W = À 1=m p;g , equation (39) can be simplified to equation (40) …”
Section: Single-side Allowance Factormentioning
confidence: 99%
“…As a result, it could be concluded that the deterioration effect of existing either one pit or multi-pits depends mainly on pitting corrosion effect rather than the alloy under investigation. In conclusion, this data is very important for the designer in order to determine the service life of machine components and structure due to economic and environmental reasons [Murakami (2002); Wulpi (2000); Klesnil and Lukas (1980); Koterazawa (1990)]. The effect of pitting on crack initiation and propagation during the fatigue test has been studied.…”
Section: Fatigue Behavior Of Ss 304mentioning
confidence: 99%